2011
DOI: 10.1007/s00348-011-1153-8
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic-PIV measurement of the flow around a zigzag boundary layer trip

Abstract: Tomographic-PIV was used to measure the boundary layer transition forced by a zigzag trip. The resulting instantaneous three-dimensional velocity distributions are used to quantitatively visualize the flow structures. They reveal undulating spanwise vortices directly behind the trip, which break up into individual arches and then develop into the hairpin-like structures typical of wallbounded turbulence. Compared to the instantaneous flow structure, the structure of the average velocity field is very different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…At intermediate α, the Reynolds shear stress distributions become approximately constant starting at values beyond 0.02 and converging to values close to 0.005. Very similar values and trends were found in the region behind a zigzag roughness strip (Elsinga and Westerweel, 2012) and the order of magnitude corresponds with turbulent flow conditions over a flat plate (Klebanoff, 1955;Erm and Joubert, 1991;Ducros et al, 1996;de Graaff and Eaton, 2000). On the smooth surface the Reynolds shear stress values and distribution found are comparable to those found for separation bubbles on low Reynolds number airfoils (Yuan et al, Fig.…”
Section: Discussionsupporting
confidence: 76%
“…At intermediate α, the Reynolds shear stress distributions become approximately constant starting at values beyond 0.02 and converging to values close to 0.005. Very similar values and trends were found in the region behind a zigzag roughness strip (Elsinga and Westerweel, 2012) and the order of magnitude corresponds with turbulent flow conditions over a flat plate (Klebanoff, 1955;Erm and Joubert, 1991;Ducros et al, 1996;de Graaff and Eaton, 2000). On the smooth surface the Reynolds shear stress values and distribution found are comparable to those found for separation bubbles on low Reynolds number airfoils (Yuan et al, Fig.…”
Section: Discussionsupporting
confidence: 76%
“…The rotating direction of the leg-buffer structures is coherent with that of the time-averaged secondary vortex pair discussed in the mean flow organization ( § 3). It has been conjectured that the secondary vortex pair emerges as an artefact of temporal averaging of leg-buffer vortices and does not occur in the instantaneous flow organization (Elsinga & Westerweel 2012). The further intensity increase of the leg-buffer vortices gives rise to a second unique large leg-shaped vortex structure outwards (figure 7b, green dash-dot line).…”
Section: Instantaneous Flow Organizationmentioning
confidence: 99%
“…The hairpin generation mechanisms were supported from experiment by flow visualization (Smith et al 1991) and from DNS (Zhou et al 1999), and gained further credibility by observations of hairpin packets in the boundary layer transition region (e.g. Wu 2010; Elsinga & Westerweel 2012). Kim, Sung & Adrian (2008) later confirmed that hairpins can auto-generate new hairpins within a fully turbulent environment, but still they had to forcefully introduce a very strong initial hairpin vortex structure into their turbulent channel flow.…”
mentioning
confidence: 90%